Fully-resolved simulations of coal particle combustion using a detailed multi-step approach for heterogeneous kinetics. (15th March 2019) - Tufano, G.L.; Stein, O.T.; Kronenburg, A.; Gentile, G.; Stagni, A.; Frassoldati, A.; Faravelli, T.; Kempf, A.M.; Vascellari, M.; Hasse, C.
Abstract: Fully-resolved simulations of the heating, ignition, volatile flame combustion and char conversion of single coal particles in convective gas environments are conducted and compared to experimental data (Molina and Shaddix, 2007). This work extends a previous computational study (Tufano et al., 2016) by adding a significant level of model fidelity and generality, in particular with regard to the particle interior description and heterogeneous kinetics. The model considers the elemental analysis of the given coal and interpolates its properties by linear superposition of a set of reference coals. The improved model description alleviates previously made assumptions of single-step pyrolysis, fixed volatile composition and simplified particle interior properties, and it allows for the consideration of char conversion. The results show that the burning behavior is affected by the oxygen concentration, i.e. for enhanced oxygen levels ignition occurs in a single step, whereas decreasing the oxygen content leads to a two-stage ignition process. Char conversion becomes dominant once the volatiles have been depleted, but also causes noticeable deviations of temperature, released mass, and overall particle conversion during devolatilization already, indicating an overlap of the two stages of coal conversion which are usually considered to be consecutive. The complex pyrolysis model leads to non-monotonous profiles of the combustion quantities which introduce a minor dependency of the ignition delay time τ ign on its definition. Regardless of the chosen extraction method, the simulations capture the measured values of τ ign very well.